Protective and curative effects of unconjugated bilirubin on gene expression of LOX-1 and iNOS in the heart of rats receiving high-fat diet and low dose streptozotocin: a histomorphometric approach - Mohammad Hasan Maleki; Omid Vakili; Ramin Tavakoli; Elham Nadimi; Zahra Noori; Motahareh Taghizadeh; Amirreza Dehghanian; Lobat Tayebi; Sayed Mohammad Shafiee (BMC, 2024)
Abstract Background Atherosclerosis is a chronic inflammatory condition affecting the large arteries and is a major cause of cardiovascular diseases (CVDs) globally. Increased levels of adhesion molecules in cardiac tissue serve as prognostic markers for coronary artery occlusion risk. Given the antioxidant properties of bilirubin and its inverse correlation with atherosclerosis, this study aimed to assess the beneficial effects of bilirubin on atherosclerotic indices and heart structure in high-fat diet-fed diabetic rats with atherosclerosis. Methods Atherosclerosis was induced in three out of five groups of adult male Sprague Dawley rats through a 14-week period of high-fat diet (HFD) consumption and a single low dose of streptozotocin (STZ) (35 mg/kg). The atherosclerotic rats were then treated with intraperitoneal administration of 10 mg/kg/day bilirubin for either 6 or 14 weeks (treated and protected groups, respectively), or the vehicle. Two additional groups served as the control and bilirubin-treated rats. Subsequently, the mRNA expression levels of vascular cell adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1), lectin-like LDL receptor 1 (LOX-1), and the inducible nitric oxide synthase (iNOS) were analyzed using quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR). Histopathological and stereological analyses were performed to assess changes in the heart structure. Results Bilirubin significantly decreased the expression of VCAM-1, ICAM-1, LOX-1, and iNOS genes in the treated group. Moreover, bilirubin mitigated pathological damage in the left ventricle of the heart. Stereological analysis revealed a decrease in the left ventricle and myocardium volume, accompanied by an increase in vessel volume in rats treated with bilirubin. Conclusion These findings demonstrate that mild hyperbilirubinemia can protect against the progression of atherosclerosis and heart failure by improving lipid profile, modulating adhesion molecules, LOX-1, and iNOS gene expression levels.